Bibliography of the exact sciences in the Low Countries from ca. 1470 to the Golden Age (1700) - Hoogendoorn, Klaas (Brill/Hes & de Graaf, 2018)
"In this annexe to the Bibliography of the exact sciences in the Low Countries, Klaas Hoogendoorn gives a detailed analytical description by autopsy of printed calendars, almanacs and prognostications by authors of the Low Countries from ca. 1470 to the Golden Age (1700). Locations of the books are given as well as secondary bibliographical sources and concise biographical data about the authors. An index on editions by printer conclude the work. Since only few copies of these ephemera have survived this annexe can be seen as the most complete census available so far. It is part of a much corrected and enlarged update of D. Bierens de Haan's 'Bibliographie néerlandaise historique-scientifique ... ', Rome, 1883 for the period to about 1700"--